Efektivitas Peran Pemerintah Desa dan Tokoh Masyarakat dalam Penyelesaian Perkara Non-Litigasi di Desa Jarin - Vianti Nur Mauliddya Ike Safitri; Moh. Soleh (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2024)
Indonesia is an archipelago with diverse languages, ethnicities, religions and cultural tribes. Although there are many differences, Indonesian citizens always uphold kinship, tolerance and harmony in their environment. This is in accordance with the motto of the Indonesian nation, namely “Bhineka Tunggal Ika” which describes the diversity of the Indonesian nation, but still one. In dispute resolution, in addition to legal channels, another form of dispute resolution in the form of alternative out-of-court settlements, which is often used by the Indonesian people, is the concept of mediation. One example of its application is in Jarin Village, Pamekasan, which resolves disputes through a negotiation process to obtain a peaceful agreement. The parties to the dispute are assisted by mediators, who are played by the village government and community leaders who are respected by the community. The form of research method used is Empirical. The research data comes from field samples that will be analyzed in a qualitative description. The results of the research are used to determine how effective mediation is in resolving disputes non-litigatively or without legal and/or judicial channels.